Tinjauan Yuridis Hak Asuh Anak (Hadhonah) Pasca Perceraian Orang Tua Akibat Kekerasan Dalam Rumah Tangga (KDRT) - Bella, Zara Zerina; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Child custody is a central issue in child protection after divorce, especially when divorce is motivated by domestic violence. Divorce cases accompanied by child custody disputes continue to increase in religious courts. Judges are obligated to examine evidence and facts revealed during the trial and prioritize the best interests of the child, guided by the Marriage Law, the Compilation of Islamic Law, the Child Protection Law, and Supreme Court jurisprudence. This normative juridical research focuses on literature review, regulatory analysis, and examination of court jurisprudence regarding child custody cases after divorce due to domestic violence. The findings indicate that child protection in custody cases related to domestic violence has not been optimal. This ineffectiveness is caused by limited evidence because domestic violence often occurs in private without witnesses, minimal public participation, limited judicial insight into the psychological impact of domestic violence, and lack of involvement of multidisciplinary experts such as psychologists, social workers, and counselors. Strengthening judges' capacity, increasing the role of experts, and procedural reforms are needed to ensure more effective and fair child protection.